Potret Tokoh Perempuan dalam Novel "Tanah Tabu" Suatu Tinjauan Objektif - Muntihanah Muntihanah (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Novel Tanah Tab, wrote by Anindita S. Thayf is a novel attempt to describe ethnographic reality of what happened in the Land of Papua. Mama Mabel as a main character called Papua as sacred land or taboo land. Political reality, the reality of a patriarchal culture that marginalize the wife in the household, the reality some people are disappointed with the presence of Timika gold mining, and reality that officers are sometimes wrong actions in dealing with the problem in Papua, Papuan people and the denial in part on immigrant communities into an interesting story to be analyzed.The purpose of the analysis is novel Tanah Tabu to enrich the reader and give an overview of the events that are taking place in the Earth Cenderawasih. Despite only using intrinsic theory and methodology of all the descriptive analysis of the facts described trying analyzed. The results of the analysis of the novel is indeed the Land Tabu two different sides. First, the main character who has a charismatic figure, intelligent, critical, daring, and a fighter is a Mama named Mabel. Mama Mabel's and drives all of the events and issues in the novel. Being female besides Mama Mabel, which Mama Helda and overview of Papuan women traders, is the image of women that is so sad. They are marginalized by her own husband, beaten, serve because they have bought, considered as a fairness and has been going on for generations wihtout them able to get out of the circle.